Adult attention-deficit hyperactivity disorder: key conceptual issues. (June 2016) - Asherson, Philip; Buitelaar, Jan; Faraone, Stephen V; Rohde, Luis A
Summary: For many years, attention-deficit hyperactivity disorder (ADHD) was thought to be a childhood-onset disorder that has a limited effect on adult psychopathology. However, the symptoms and impairments that define ADHD often affect the adult population, with similar responses to drugs such as methylphenidate, dexamphetamine, and atomoxetine, and psychosocial interventions, to those seen in children and adolescents. As a result, awareness of ADHD in adults has rapidly increased and new clinical practice has emerged across the world. Despite this progress, treatment of adult ADHD in Europe and many other regions of the world is not yet common practice, and diagnostic services are often unavailable or restricted to a few specialist centres. This situation is remarkable given the strong evidence base for safe and effective treatments. Here we address some of the key conceptual issues surrounding the diagnosis of ADHD relevant to practising health-care professionals working with adult populations. We conclude that ADHD should be recognised in the same way as other common adult mental health disorders, and that failure to recognise and treat ADHD is detrimental to the wellbeing of many patients seeking help for common mental health problems.